Soul, heart and life of Dispute Boards: thoughts about its regulation in Latin America and Peru - Cuentas Pino, Daniel (2022)
This paper aims to (i) define the Dispute Board; (ii) expose the advantages of Dispute Boards in the field of engineering and construction; (iii) analyze the Latin American regulatory framework that deals with Dispute Boards; (iv) offer a scientific-practical analysis of the Peruvian regulatory case with respect to Dispute Boards, where the influence of Legislative Decree 1444 is highlighted; (v) provide reflections based on the relationship between Dispute Boards and arbitration; (vi) set out the potentially controversial points of the actual application of Dispute Boards; and (vii) review the new initiatives that are committed to promoting and disseminating knowledge, both in Latin America and Spain, etc.